A randomized, double-blind, and placebo-controlled study with tranexamic acid of bleeding and fibrinolytic activity after primary coronary artery bypass grafting - Santos,A.T.L. (2006)
Cardiopulmonary bypass is frequently associated with excessive blood loss. Platelet dysfunction is the main cause of non-surgical bleeding after open-heart surgery. We randomized 65 patients in a double-blind fashion to receive tranexamic acid or placebo in order to determine whether antifibrinolytic therapy reduces chest tube drainage. The tranexamic acid group received an intravenous loading dose of 10 mg/kg, before the skin incision, followed by a continuous infusion of 1 mg kg-1 h-1 for 5 h. The placebo group received a bolus of normal saline solution and continuous infusion of normal saline for 5 h. Postoperative bleeding and fibrinolytic activity were assessed. Hematologic data, convulsive seizures, allogeneic transfusion, occurrence of myocardial infarction, mortality, allergic reactions, postoperative renal insufficiency, and reopening rate were also evaluated. The placebo group had a greater postoperative blood loss (median (25th to 75th percentile) 12 h after surgery (540 (350-750) vs 300 (250-455) mL, P = 0.001). The placebo group also had greater blood loss 24 h after surgery (800 (520-1050) vs 500 (415-725) mL, P = 0.008). There was a significant increase in plasma D-dimer levels after coronary artery bypass grafting only in patients of the placebo group, whereas no significant changes were observed in the group treated with tranexamic acid. The D-dimer levels were 1057 (1025-1100) µg/L in the placebo group and 520 (435-837) µg/L in the tranexamic acid group (P = 0.01). We conclude that tranexamic acid effectively reduces postoperative bleeding and fibrinolysis in patients undergoing first-time coronary artery bypass grafting compared to placebo.